Photography in dentistry: Part II (Intraoral photography) - Mirfazaelian A; Siadat H (Tehran University of Medical Sciences, 2006)
In addition to the camera, other accessories such as retractors and mirrors are necessary for intraoral photography. They enable directly inaccessible subjects, to be viewed and photographed easily. Gaining adequate view, by suitable retractors and mirrors, is the most important step, requiring skill and patient cooperation to achieve successful results. Composition, visualization of the final photograph and a carefully controlled clinical technique must be practiced in order to produce rapid, precise and reproducible clinical photographs. There are many procedures to be followed and precautions to be taken in order to obtain good quality, reproducible dental photographs. Failures can be avoided by following a distinct procedure. This article focuses on clinical equipments such as retractors, mirrors and intraoral photography.